A companion to Anglican eucharistic theology. - Douglas, Brian (Religious Studies, Theology and Philosophy E-Books Online, Collection 2012, ISBN: 9789004223301., 2012)
Anglican eucharistic theology varies between the different philosophical assumptions of realism and nominalism. Whereas realism links the signs of the Eucharist with what they signify in a real way, nominalism sees these signs as reminders only of past and completed transaction. This book begins by discussing the multifomity of the philosophical assumptions underlying Anglican eucharistic theology and goes on to present case extensive study material which exemplify these different assumptions from the 20th Century to the Present. By examining the multiformity of philosophical assumptions this book avoids the hermeneutic idealism of particular church parties and looks instead at the Anglican eucharistic tradition in a more critical manner.